Innovative Housing Policy Tools for Local Governments in Shrinking Communities with a Large Share of Privately Owned Apartments: A Case Study of Valga, Estonia - Jiri Tintera (Transylvanian Review of Administrative Sciences, 2019)
Shrinking communities face a myriad number of problems. The physical manifestation of urban shrinkage can best be noted in abandoned or underutilized properties, an oversupply or deteriorating housing stock and inadequate aging infrastructure. These physical manifestations lead to psychological impacts of poor perception of a community, lack of a sense of place, lethargic residents who lack the financial means or motivation to improve their living conditions. Planning for the regeneration and rightsizing of shrinking communities calls for intervention by government sectors. Valga is a small town in Estonia where housing vacancies, low quality of residential premises and the shortage of quality apartments are the result of decades of depopulation. As a result of housing privatization after the collapse of the Soviet Union, a large majority of the dwellings are privately owned. Housing demolitions and revitalization are a key part of the small town’s strategy to deal with shrinkage. This paper addresses the question: in an area of urban shrinkage, what kind of housing policy can local government create in the conditions of prevailing private ownership of residential premises? Drawing on a qualitative case study of the town of Valga, the findings show that housing policy plays an important role in urban recovery for a shrinking community and the leadership capacity of local government in this process is critical. Ownership constrains in housing policy can be overcome but the lack of municipal finance and human resources together with insufficient legislation and missing cooperation with the private sector impedes the process.